Confidentiality in foreign investment arbitration and the public’s interest - Bravo, Bárbara Magalhães (2018)
Due to the actual economic and political European situation as well as economic globalization there has been an increase of foreign investment, promoted by the liberalization of market and capitals with the objective of promoting economical growth in the States. The investors find many obstacles such as public expropriations, tax increase, restrictions upon the withdraw of foreign investment. These situations can became litigious. The foreign investment arbitration, as an alternative for resolution of litigious, due to all of the advantages, such as efficiency, specialization of the arbitrators and impartiality are a big incentive to foreign investment. Although, the confidentiality in foreign investment arbitration imposes some questions. In this sense, the United Nations Commission in International Trade Law (UNCITRAL) in 2013, having in mind the public interest referring to the arbitrations enacted some transparency rules. This is a model law that is a Soft Law, allowing States to adopt these measures internally or complementing there procedures with some norms instilled in the model law. On other hand, it´s urgent to create mechanisms that are effective in transparency, on the other hand protect the public interest and the guaranty of protection of the investors’ interest. For we wish to find a solution that articulates the transparency principle and public interest in arbitral procedure. We want to show case through juridical arbitral analysis, which is the best criteria to solve the conflict between the confidentiality of arbitral procedure/public interest. The foreign investment juridical relations impose just as in international contracts, confidentiality, proper for arbitration. However, due to the fact that one of the subjects is the State and the only interest, it must have is the public interest. Thus should observe the principle of transparency as it is one of the main principles of the administrative law. In this sense there should be an adequate alternative solution for resolving conflicts, furthermore to allow all subjects to follow the arbitral procedure. The arbitral awards that involve the States and foreign investors can origin profound consequences for citizens, for example, forcing the administration to pay indemnities witch will have negative consequences to the State’s budget, and this brings negative effects to our communities. It’s important to adopt mechanisms in the national supra national legislation that level the arbitral procedure secrecy, without questioning the public interest in foreign investment. It is important to balance all the interests at stake and find a solution that does not harm foreign investment and also protects the public interest.